2004
DOI: 10.1007/s00425-003-1200-7
|View full text |Cite
|
Sign up to set email alerts
|

Formation of unidentified nitrogen in plants: an implication for a novel nitrogen metabolism

Abstract: Plants take up inorganic nitrogen and store it unchanged or convert it to organic forms. The nitrogen in such organic compounds is stoichiometrically recoverable by the Kjeldahl method. The sum of inorganic nitrogen and Kjeldahl nitrogen has long been known to equal the total nitrogen in plants. However, in our attempt to study the mechanism of nitrogen dioxide (NO(2)) metabolism, we unexpectedly discovered that about one-third of the total nitrogen derived from (15)N-labeled NO(2) taken up by Arabidopsis thal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…The seedlings of both groups were grown for 10 d more and irrigated with 50 ml of 0.1% Hyponex containing 20 µM CdCl 2 every 4 d. Plants were then harvested, washed with pure water, and separated into leaves, stems, and roots. Harvested organs were separately lyophilized, powdered, and stored in a desiccator until use (Morikawa et al, 2004;Takahashi et al, 2001).…”
Section: Plant Materials and Growthmentioning
confidence: 99%
“…The seedlings of both groups were grown for 10 d more and irrigated with 50 ml of 0.1% Hyponex containing 20 µM CdCl 2 every 4 d. Plants were then harvested, washed with pure water, and separated into leaves, stems, and roots. Harvested organs were separately lyophilized, powdered, and stored in a desiccator until use (Morikawa et al, 2004;Takahashi et al, 2001).…”
Section: Plant Materials and Growthmentioning
confidence: 99%
“…1A) was mainly explained by the important increase of the hydrolyzable unidentified N (HU-N, 66.3%), which was likely due to the recent incorporation of plant phytomass because: (1) this fraction comprises a substantial proportion of total N in many plant species (Morikawa et al, 2004), and (2) most of this unidentified N from plant materials is extracted with H1 (González- Prieto et al, 1995a, b). The augment in HU-N, and to a lesser extent that in amino acid N (AA-N, 11.2%), counterbalanced the significant reduction observed in the amide (AM-N, 33.2%) and the amino sugar fractions (AS-N, 68.0%) (Fig.…”
Section: Organic N Distribution In the Natural And The Labelled Soilmentioning
confidence: 99%
“…27 We also reported that some NO 2 -derived nitrogen is converted into oxidized nitrogen compounds, such as nitro and nitroso compounds. 28,29 Therefore, nitrated proteins might play a role in the cellular signaling underlying NO 2 -regulated plant growth.…”
mentioning
confidence: 99%